YAP-independent mechanotransduction drives breast cancer progression - Joanna Y. Lee (Nature Portfolio, 2019)
The transcriptional regulator YAP is regarded as the universal mechanotransducer, largely from 2D culture studies. Here the authors show that in breast cancer patient tissues and cells in 3D culture, mechanical signals are transduced independently of YAP, questioning YAP as a therapeutic target.